2020
DOI: 10.1097/ico.0000000000002383
|View full text |Cite
|
Sign up to set email alerts
|

Tear Opiorphin Levels in Ocular Pain Caused by Corneal Foreign Body

Abstract: Purpose: Opiorphin is an endogenous inhibitor of enkephalin-degrading enzymes. It has a strong analgesic effect in chemical and mechanical pain models. We aimed to evaluate the tear opiorphin levels in ocular pain caused by corneal foreign bodies and demonstrate whether there is any correlation with pain levels obtained from the Visual Analog Scale (VAS) score and tear opiorphin level. Methods: Thirty-two healthy individuals and 34 individuals diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…Salaric et al reported an increase in salivary opiorphin in patients with burning mouth syndrome [ 33 ], while, more recently, Ozdogan et al described an increase in salivary opiorphin in patients with dental pain caused by pulp inflammation [ 34 ]. Opiorphin levels were reported to be increased in the tears of patients with ocular pain caused by a corneal foreign body [ 35 ]. This suggests that opiorphin may play a role in the modulation of orofacial and eye pain [ 8 , 35 ].…”
Section: Opiorphinmentioning
confidence: 99%
See 1 more Smart Citation
“…Salaric et al reported an increase in salivary opiorphin in patients with burning mouth syndrome [ 33 ], while, more recently, Ozdogan et al described an increase in salivary opiorphin in patients with dental pain caused by pulp inflammation [ 34 ]. Opiorphin levels were reported to be increased in the tears of patients with ocular pain caused by a corneal foreign body [ 35 ]. This suggests that opiorphin may play a role in the modulation of orofacial and eye pain [ 8 , 35 ].…”
Section: Opiorphinmentioning
confidence: 99%
“…Opiorphin levels were reported to be increased in the tears of patients with ocular pain caused by a corneal foreign body [ 35 ]. This suggests that opiorphin may play a role in the modulation of orofacial and eye pain [ 8 , 35 ]. Opiorphin reduces pain caused by different origins in a manner comparable, if not greater, to morphine in terms of both efficacy and potency [ 30 , 36 ].…”
Section: Opiorphinmentioning
confidence: 99%
“…Inflammation of the ocular surface can result in damage to the corneal sub-basal nerve plexus, which detects mechanical, thermal, and chemical stimuli, and generates output perceivable as pain or a range of dysesthesias [34]. Our results indicated the presence of opiorphin in the protein supply of GlicoPro at the same concentration that is normally present in tears [12]. This peptide, which acts as a natural potent non-opioid endogenous analgesic, may have therapeutic effects on the neurosensory abnormalities responsible for DED symptoms such as NP.…”
Section: Discussionmentioning
confidence: 70%
“…Opiorphin is also secreted in tears, where it prevents the degradation of encephalins, and thus inhibits pain perception [10,11]. Ozdogan et al reported that opiorphin levels are increased in patients diagnosed with corneal foreign objects compared with healthy individuals, suggesting that opiorphin secretion increases in response to pain [12].…”
Section: Introductionmentioning
confidence: 99%
“…Enkephalins are associated with an analgesic effect, but their action is relatively short-lived due to the presence of enzymes that rapidly degrade these neuropeptides. Endogenous inhibitors of enkephalin enzymes do exist and are present in foreign body models of ocular pain (Ozdogan et al, 2020;Lasagni Vitar et al, 2021). Thus, pharmacologic inhibition of such enzymes may be a therapeutic target.…”
Section: Topical Enkephalin Modulators: Future Targetsmentioning
confidence: 99%